A Comparison of Common Hippopotamus (Artiodactyla) and Mysticete (Cetacea) Nostrils: An Open and Shut Case. Issue 5 (8th December 2018) - Maust‐Mohl, Maria; Reiss, Diana; Reidenberg, Joy S.
ABSTRACT: Hippos are considered the closest living relatives to cetaceans and they have some similar adaptations for aquatic living, such as a modified respiratory tract. Behavioral observations of male and female common hippos ( Hippopotamus amphibius ) at Disney's Animal Kingdom® and the Adventure Aquarium were conducted to describe and examine movements of the nostrils during respiration (inspiration, expiration, and inter‐breath interval). The hippo nostril is a crescent shaped opening with lateral and medial aspects that are mobile and can be adducted and abducted to regulate the nostril opening. Notably, the default (resting) position of the nostrils is closed during the inter‐breath interval, even when hippos are resting in water and their heads are not submerged. Similar to cetaceans, this aquatic adaptation protects the respiratory tract from an accidental incursion of water that can occur even when the nostrils are above water. Dissection of a deceased captive common hippo suggests there are separate muscles that pull the medial and lateral aspects for abduction. The internal nasal passage has a nasal plug that is similar in shape but less pronounced than the nasal plugs of two baleen whale species studied (minke whale Balaenoptera acutorostrata, fin whale Balaenoptera physalus ). Examination of the musculature suggests fibers attach from the premaxillae and extend caudally to retract the plug to open the nasal passage. We discuss similarities and differences of the nostrils/blowholes of fully aquatic, semi‐aquatic, and terrestrial species to assess adaptations related to environmental conditions that may be convergent or derived from a common ancestor. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc. Anat Rec, 302:693–702, 2019. © 2018 Wiley Periodicals, Inc.